On the noncompactness of classes of mappings with restrictions on dilation in measure - Potemkin, V. L.; Ryazanov, V. I. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We establish that the classes of mappings with restrictions in measure cannot be compact except for certain degenerate cases. In particular, this implies that any David class ΓI is noncompact.